RESORT DEVELOPMENT IN FACING TREND AND TECHNOLOGICAL CHANGES - Sahea, Gabriela R.; Saerang, David P. E.; Pandowo, Merinda H.C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
Resort and Hotel is biggest tourism industry business in Manado. Resort and Hotel as a whole is always evolving because of the trends within this industry. Industry In the current situation. This business needs to do well and take advantage of the very rapid developments in the world. Not only do they have to compete with each other but they also have to survive in order to keep their business on the never ending trend and technological developments that occur in the world, especially in Manado. This research aims to obtain a more comprehensive understanding of where these determinants influence the development of a resort, whether a major impact on human lifestyle such as attitude or not. This research uses qualitative methods and multiple linear regression analysis as a tool to analyze the data that has been collected. The results of this study indicate that the independent variables, namely Trend and Technology, simultaneously influence a resort. There are several solutions offered to these problems such as business incubators and the use of technology such as internet platforms and e-commerce from leading companies can be one of the main ways for a business to survive.Â Keyword: trend, technological, development